Are the Appropriate Use Criteria for the management of pediatric supracondylar humerus fractures useful in clinical practice?. Issue 5 (September 2017) - Kazimoglu, Cemal; Turgut, Ali; Reisoglu, Ali; Kalenderer, Önder; Önvural, Burak; Agus, Haluk
Abstract : The aim of this study was to evaluate our treatment modalities in pediatric supracondylar humerus fractures according to the recently published Appropriate Use Criteria (AUC) by the American Academy of Orthopaedic Surgeons. A total of 991 patients with supracondylar humerus fractures were included. After reviewing medical records, 38 different clinical scenarios described in the AUC were observed. Of the 991 patients, 127 were type I, 423 were type II, and 405 were type III fractures according to the Gartland classification. The AUC was appropriate for 100% of type I, only 25 (5.9%) of type II, and 389 (96.0%) of type III fractures. Overall, the total appropriateness rate was 54.5%. We concluded that application of the AUC is useful but burdensome and that AUC provides important guidance especially for rarely encountered urgent clinical scenarios.